Engagement in learning among kindergarten students (Journal of the College of Basic Education, 2023)
Summary of the research:The current research aims to identify the degree of engagement in learning among kindergarten students. Where the researcher prepared a scale to measure engagement in learning, where this scale in its final form consisted of (37) items distributed over five domains, (active cooperative learning, student effort, academic challenges, student interactions with the teaching staff, support for learners) and the paragraphs were divided into Domains The first domain had 7 paragraphs, the second 8 paragraphs, the third 9 paragraphs, the fourth 6 paragraphs, and finally, the fifth domain included 7 paragraphs. In a random way, the validity and reliability of the scale were verified by extracting the validity using the apparent validity method and the constructive validity method. As for the reliability, it was extracted using the re-test method and the Vakronbach coefficient, and the results showed that the research sample members are characterized by their involvement in learning. Involvement in learning is the effort exerted, whether it is scientific or physical effort, and the use of all available cognitive strategies to make education characterized by clarity. It is also considered an important factor in student progress as well as an important essential element for developing the learning process and a means to enhance the results of academic achievement and address the problem of failure. Academic.Keywords: Engagement in learning, kindergarten students.